SOCIAL RESPONSIBILITY PROJECTS: A CASE STUDY IN THE COMPANY AGROVALE JUAZEIRO-BA - Ávila Ribeiro, Kleber; Agnacilda de Azevedo, Elaine; Anne granja torres, Shirlei (Revista Desenvolvimento Social, 2020)
This aims to show how the social programs developed by Agrovale company, from 2007 to 2011 in the city of Juazeiro-BA, has contributed to the professional development of its employees and the consequences of their actions on quality of life of its employees and the community in which is inserted. For the preparation of the research, a sample was used consisting of 80 people, including employees, dependents and community members in general. The criterion for the scope of the research was to have been benefited by at least one of the social programs implemented by the company. The survey showed that the investigated company has contributed to the social and economic development of not only the employees, but to improve the quality of life of the whole community that their projects benefit.